Homicide [videorecording (DVD)] - Mamet, David; Mamet, David; Mantegna, Joe; Macy, William H., 1950-; Nogulich, Natalia; Rhames, Ving, 1961- (Criterion collection, 2009)
An inner-city detective is investigating the murder of an elderly candy shop owner and finds odd clues along the way, while at the same time trying to find out who he has become.